Distribution patterns of dung beetle (Coleoptera: Scarabaeidae) assemblages in croplands and pastures across two climatic zones of Pakistan. (3rd July 2022) - Hussain, Mubashar; Kanwal, Maimoona; Aftab, Kiran; Khalid, Maryam; Liaqat, Somia; Iqbal, Tahir; Rahman, Ghani; Umar, Muhammad
ABSTRACT: We explored patterns of dung beetle diversity from croplands and pastures in two climatic zones (hot semi-arid and humid subtropical climate) from six localities in each of three districts, i.e. Gujrat, Kotli and Sialkot. We placed three 500 m long transects each separated by ~150 m apart within a sampling site. Data were collected by placing nine pitfall traps, each separated by ~50 m apart at each habitat. We estimated alpha diversity metrics and also calculated the similarity percentage (SIMPER) between study sites and habitat types. Nineteen species representing eight genera, six tribes and two subfamilies were recorded. Dung beetle assemblages showed significant differences in relative abundance in species richness and abundance. In croplands, Onthophagus gazella (18.19%), Onitis philemon (09%) and Onitis castaneous (12.92%) were the most abundant species. Whereas in pastures, Onthophagus gazella (11.16%), Onitis castaneous (6.65%) and Onitis philemon (8.22%) were abundant. SIMPER results indicated that Onthophagus gazella and Onitis castaneous were top contributors in the dissimilarity between study sites and habitat types. Greater diversity was recorded in Gujrat and Kotli Tunnellers were the most dominant functional guild in both habitat types. The present study highlights that climatic zones influence the patterns of distribution of dung beetle assemblages associated with habitat types.